The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1152/ajprenal.00495.2012
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor of activated T cells mediates RhoA-induced fibronectin upregulation in glomerular podocytes

Abstract: Glomerulosclerosis is featured by accumulation of the extracellular matrixes in the glomerulus. We showed previously that activation of the small GTPase RhoA in podocytes induces heavy proteinuria and glomerulosclerosis in the mouse. In the current study, we investigated the mechanism by which RhoA stimulates the production of one of the extracellular matrixes, fibronectin, by podocytes, specifically testing the role of nuclear factor of activated T cells (NFAT). Expression of constitutively active RhoA in cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 85 publications
1
11
0
Order By: Relevance
“…Jiang et al [44] utilized RhoA inhibitors to suppress the effect of TRPC6 over-expression, implicating RhoA as an important component in TRPC6-induced proteinuria, derangement of podocyte cytoskeleton, decreased expression of nephrin and foot process effacement. Zhu et al [45] also showed that TRPC6 overexpression increases podocyte intracellular calcium to activate RhoA signaling pathways and subsequent kidney damage.…”
Section: Discussionmentioning
confidence: 98%
“…Jiang et al [44] utilized RhoA inhibitors to suppress the effect of TRPC6 over-expression, implicating RhoA as an important component in TRPC6-induced proteinuria, derangement of podocyte cytoskeleton, decreased expression of nephrin and foot process effacement. Zhu et al [45] also showed that TRPC6 overexpression increases podocyte intracellular calcium to activate RhoA signaling pathways and subsequent kidney damage.…”
Section: Discussionmentioning
confidence: 98%
“…These data from cultured podocytes may suggest that the activation of RhoA has a negative impact on podocyte morphology and (or) function. In addition, the albumin-induced transactivation of the endothelin-1 gene in mouse podocytes was dependent on ROCK (Morigi et al 2005), and RhoA-induced activation of the nuclear factor of activated T-cells was shown to contribute to fibronectin gene transactivation in podocytes (Zhu et al 2013). Thus the activation of RhoA may also transactivate pathogenic genes in podocytes.…”
Section: Rhoa In Podocytes: Findings From Cultured Cellsmentioning
confidence: 97%
“…In addition, downregulation of nephrin and synaptopodin was demonstrated, which could contribute to proteinuria (Wang et al 2012a). Furthermore, when the expression level of constitutively active RhoA was high it upregulated fibronectin expression and subsequent glomerulosclerosis, possibly via the calcium-calmodulin-calcineurin-NFAT pathway (Zhu et al 2011(Zhu et al , 2013. In the latter context, overexpression of the ECM protein, fibronectin, by injured/simulated podocytes may be indicative of an epithelial-mesenchymal transition to avoid apoptotic cell death (Kang et al 2010).…”
Section: Rhoa In Transgenic Micementioning
confidence: 99%
“…When TRPC6 or its upstream signal is blocked, podocyte injury can be alleviated. [26][27][28][29] Connexin43 (Cx43) is a major component of gap junctions (Gjs) and hemichannels, plays a unique role in intracellular communication by directly permitting substances such as calcium, ATP in-and-out of cells. Cx43 also localizes on podocyte SD.…”
Section: Calcium Ion Channel and Downstream Signaling Pathways In Hypmentioning
confidence: 99%